Student quest : criação de uma ferramenta de gamificação para ambiente virtual de aprendizagem baseada em narrativa - Henz, Rovian Franco Antonelli (My University, 2019)
Virtual learning environments currently occupy a prominent place in educational environments. Its use together with gamification is enhancing the engagement of its users. Based on these aspects, this work presents a proposal for the application of a gamification strategy based on a narrative structure in virtual learning environments. This research seeks to use the player archetypes defined by Richard Bartle (1996), along with the gamification elements proposed by Hunter and Werbach (2012), to establish a form of gamification that can be triggered by the narrative structure of Hero's Journey, Joseph Campbell (2005) and, finally, apply in a virtual learning environment. With the results achieved it was possible to clearly visualize the application of the narrative in the gamified environment (sic).
Os ambientes virtuais de aprendizagem atualmente ocupam um espaço de destaque nos meios educacionais. Sua utilização junto à gamificação está potencializando o engajamento de seus usuários. Com base nestes aspectos, esse trabalho apresenta uma proposta para a aplicação de uma estratégia de gamificação baseada em uma estrutura narrativa em ambientes virtuais de aprendizagem. Essa pesquisa busca utilizar os arquétipos de jogadores definidos por Richard Bartle (1996), juntamente com os elementos de gamificação propostos por Hunter e Werbach (2012), para estabelecer uma forma de gamificação que possa ser acionada pela estrutura narrativa da Jornada do Herói, de Joseph Campbell (2005). Com os resultados alcançados foi possível visualizar de forma clara a aplicação da narrativa no ambiente gamificado (sic).
Keywords: Ambientes virtuais compartilhados; Aprendizagem